2020
DOI: 10.13107/jocr.2020.v10.i09.1882
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Capitellar Defect using Freeze-dried Cadaveric Allograft – A Case Report

Abstract: Allograft reconstruction of capitellar defect is an option of treatment for osteoporotic non-fixable capitellar fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…1 , 4 , 7 , 12 The incidence of ipsilateral concomitant capitellar osteochondral injury is 1%-39%. 2 , 3 , 8 , 13 , 14 , 20 Various treatment options exist for capitellar fractures including fragment excision, operative fixation, allograft reconstruction, 9 and hemiarthroplasty depending on the comminution, severity of injury, and associated fractures. 2 , 5 , 6 , 16 , 17 , 18 Although no studies have reported the use of radial head autograft for reconstruction of the capitellum, Ring et al 15 described successfully reconstructing the coronoid by using a fragment of the discarded fractured radial head to help restore ulnohumeral stability.…”
Section: Discussionmentioning
confidence: 99%
“…1 , 4 , 7 , 12 The incidence of ipsilateral concomitant capitellar osteochondral injury is 1%-39%. 2 , 3 , 8 , 13 , 14 , 20 Various treatment options exist for capitellar fractures including fragment excision, operative fixation, allograft reconstruction, 9 and hemiarthroplasty depending on the comminution, severity of injury, and associated fractures. 2 , 5 , 6 , 16 , 17 , 18 Although no studies have reported the use of radial head autograft for reconstruction of the capitellum, Ring et al 15 described successfully reconstructing the coronoid by using a fragment of the discarded fractured radial head to help restore ulnohumeral stability.…”
Section: Discussionmentioning
confidence: 99%